Email pragmatics and second language learners - Economidou-Kogetsidis, Maria; Savić, Milica; Halenko, Nicola (Pragmatics & beyond;, 2021)
"This is the first edited collection focusing exclusively on how second language users interpret and engage with the processes of email writing. With chapters written by an international array of scholars, the present volume is dedicated to furthering the study of the growing field of L2 email pragmatics and addresses a range of interesting topics that have so far received comparatively scant attention. Utilising both elicited and naturally-occurring data, the research in this volume takes the reader from a consideration of learners' pragmatic development as reflected in email writing, and their perceptions of the email medium, to relational practices in various email functions and in a variety of academic contexts. As a whole, the contributions incorporate research with learners from a range of proficiency levels, language and cultural backgrounds, and employ varied research designs in order to examine different email speech acts. The book provides valuable new insights into the dynamic and complex interplay between cultural, interlanguage, pedagogical, and medium-specific factors shaping L2 email discourse, and it is undoubtedly an important reference and resource for researchers, graduate students and experienced language teachers"--